Legal Force of Sale and Purchase Deeds Before Land Deed Officials in Proving Land Ownership Rights in Resolution of Land Disputes - Nurul Iksan, Muhammad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
This study aims to analyze the legal force of a sale and purchase deed before a Land Deed Making Official (PPAT) in proving land ownership rights and examines legal protection for land owners in resolving land disputes in Indonesia. The research method used is normative juridical with a statutory regulatory approach and a conceptual approach, using secondary data in the form of primary, secondary, and tertiary legal materials analyzed descriptively qualitatively. The results of the study indicate that the PPAT sale and purchase deed has a fundamental position as an authentic deed with perfect evidentiary power based on Article 1870 of the Civil Code, but its legal force is not absolute because it can be destroyed if there are formal or material legal defects. Legal certainty of land ownership is only fully achieved after the PPAT deed is registered and a certificate is issued in the name of the buyer. Legal protection for land owners is realized through preventive protection in the form of a Complete Systematic Land Registration (PTSL) program and an electronic-based land administration system, as well as repressive protection through dispute resolution mechanisms, both litigation and non-litigation, as regulated in UUPA Number 5 of 1960, PP Number 24 of 1997, and PP Number 37 of 1998. This study recommends the need to strengthen supervision of PPAT, accelerate the land registration program, and increase public legal awareness to realize optimal land legal certainty in Indonesia.